Factors Affecting the Implementation of the Nursing Process in Tertiary Hospitals: A Cross-Sectional Study - Nahla AbdulGadir Tayyib; Fatmah J. Alsolami (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To identify and examine the factors that hinder the effective implementation of the nursing process in tertiary health care settings in Saudi Arabia. METHODOLOGY: A descriptive cross-sectional study was conducted among 182 registered nurses with at least one year of experience in tertiary hospitals in Makkah, Saudi Arabia, recruited through hospital administration using a systematic random sampling technique A structured questionnaire, adapted from Owusu-Ansah YA and Agyeman-Yeboah J, was used to collect data on demographic characteristics and factors at the knowledge, individual, and health system levels that affect the implementation of the nursing process. Data were analyzed using descriptive statistics, and chi-square tests were performed to assess associations and predictors of barriers to the implementation of the nursing process (p < 0.001). RESULTS: Knowledge of the nursing process varied, with gaps in understanding its structured framework and care plan, while most nurses recognized its continuity, patient involvement, and role in quality care. Certain aspects of knowledge were significantly associated with academic qualification and clinical experience, whereas professional rank had minimal influence. Individual-level factors showed limited associations with qualification, rank, or experience, and health system factors were largely un-associated with nurse characteristics, except that participation in training and workshops was significantly associated with qualification and experience. CONCLUSION: The study reveals a diverse spectrum of knowledge among nurses regarding the nursing process and its components. Addressing context-specific factors that may facilitate or hinder the implementation of the nursing process is essential for effective patient care and patient safety.